Fava bean–induced hemolytic crisis in glucose-6-phosphate dehydrogenase deficiency - IPG Karyana; IB Mudita (Indonesian Pediatric Society, 2003)
This paper reports a case of hemolytic crisis dueto fava beans in a child with G6PD deficiency.